2003
DOI: 10.1063/1.1622985
|View full text |Cite
|
Sign up to set email alerts
|

Growth of cubic InN on r-plane sapphire

Abstract: Articles you may be interested inDirect growth of hexagonal InN films on 6H-SiC by radio-frequency metal-organic molecular-beam epitaxya)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 11 publications
(4 reference statements)
5
58
2
Order By: Relevance
“…41 Note that the ratio of wurtzite-to-zinc-blende-phase formation in the MBE growth of group-III nitrides strongly depends on the growth conditions, 45 which can explain the different results.…”
Section: Semipolar "101 1… Innmentioning
confidence: 94%
See 1 more Smart Citation
“…41 Note that the ratio of wurtzite-to-zinc-blende-phase formation in the MBE growth of group-III nitrides strongly depends on the growth conditions, 45 which can explain the different results.…”
Section: Semipolar "101 1… Innmentioning
confidence: 94%
“…It has been previously shown that direct growth of InN on r-plane sapphire results in the nucleation of zinc-blende InN due to the much lower lattice mismatch compared to the wurtzite InN. 41 Indeed, the HRTEM images taken from the interface region of our semipolar InN film revealed the presence of zinc-blende InN with ͑002͒ orientation at the interface with the substrate ͑Fig. 11͒.…”
Section: Semipolar "101 1… Innmentioning
confidence: 99%
“…35 In addition InN is predominantly grown as hexagonal wurtzite material rather than the more symmetric cubic zinc-blende structure, although growth of cubic InN is possible. 36 Some preliminary data on time resolved photoluminescence of InN are shown in Fig. 4 and discussed below.…”
Section: Time Resolved Photoluminescence Of Slowed Carrier Coolingmentioning
confidence: 99%
“…20 nearly equals to the spacing between {200} planes in c-InN (~2.49 Å). 25 In this work, while (Al)GaN could be grown without obvious oxidation using the MOCVD, but InN showed easily oxidizable nature, as Yoshimoto et al pointed out in MBE growth. 11 It should be noted that there's a possibility of formation of oxide precipitates in InN during MOCVD growth even in an inert gas environment such as N 2 because H 2 carrier gas generally introduced to the reactor chamber for subsequent (Al)GaN growth and H 2 produced by the decomposition of NH 3 can play the same role.…”
Section: Iiic Inn Quantum Dotsmentioning
confidence: 87%